Towards Privacy by Design on the Internet of Things (IoT) Use: A Qualitative Descriptive Study - Ahmad Luthfi; Emigawaty Emigawaty (Journal of Information System and Informatics, 2022)
From remote control and surveillance to energy and health monitoring, IoT devices provide cutting-edge services to improve our lives. Nevertheless, IoT technologies raise complicated, innovative privacy-related issues that might limit their widespread adoption. Due to the passive nature of many IoT devices, it may be challenging for users to understand that their personal information is being gathered. Therefore, this paper aims to examine the Privacy by Design IoT application idea. We adapted the seven principles of Ann Cavoukian's Privacy by Design, which were first developed. In this study's qualitative descriptive methodology with interview sections are used. The results indicate that the majority of IoT users agree with and have high expectations for the Privacy by Design concept to be one of the remedies to the imbalance between concerns about the risks and benefits of using IoT.